2018
DOI: 10.1080/2159676x.2018.1479980
|View full text |Cite
|
Sign up to set email alerts
|

The promise of glitching bodies in sport: a posthumanist exploration of an intersex phenomenon

Abstract: This paper is about glitching bodies-bodies that break, crash and confuse the conventions of pre-programmed and binary gender patterns. Exploring the promise of an intersex phenomenon; hyperandrogenism in women's sport, I discuss how glitching bodies and a feminist posthumanist understanding of gender can contribute to the field of gender and queer sport studies. Responding to calls for research enacting how non-binary bodies challenge the dualistic gendered ontologies that have structured the performative pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…We thus delineate that, given the referendum on marriage equality focused on same-sex marriage, we are most specifically talking about gays and lesbians. We also do this in order to avoid generalising results from these populations onto bisexual and transgender athletes, for whom there is little research (Anderson and Travers, 2017), as well as for intersex athletes, for whom there is also very little research (Linghede, 2018). We argue that collapsing these disparate groups homogenises their experiences as one, erasing important and often striking differences between them (Worthen, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…We thus delineate that, given the referendum on marriage equality focused on same-sex marriage, we are most specifically talking about gays and lesbians. We also do this in order to avoid generalising results from these populations onto bisexual and transgender athletes, for whom there is little research (Anderson and Travers, 2017), as well as for intersex athletes, for whom there is also very little research (Linghede, 2018). We argue that collapsing these disparate groups homogenises their experiences as one, erasing important and often striking differences between them (Worthen, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Returning to queer feminism and sport, in a posthumanist analysis of hyperandrogenism in women's sport, Linghede (2018) focuses on glitching bodies, specifically intersex bodies that 'break, crash and confuse the conventions of preprogrammed and binary gender patterns' (p. 570). Applying existing sport feminist arguments: 'Over and again it has been found that some athletic bodies cannot adjust to sporting and scientific sex classifications' (p. 573).…”
Section: Queer Theory and Transfeminismmentioning
confidence: 99%
“…To truly challenge how we write, we must first experiment with new ways of thinking, a process optimised through contact with different literatures. In the sport sciences, there is a growing body of literature that youth sport researchers can access touching on assemblage (e.g., Camiré, 2021) but also postqualitative inquiry (e.g., Beggan, 2022; Monforte & Smith, 2021), new materialism (Monforte, 2018; Thorpe et al, 2020), and posthumanism (e.g., Linghede, 2018). Youth sport researchers should also consult the 2021 double issue in Somatechnics devoted to sport, physical culture, and new materialisms exploring intriguing topics such as materiality in coaching, athleisure, and Indigenous materialisms.…”
Section: Implications For Youth Sport Researchmentioning
confidence: 99%